Beberapa Dokumen Tentang Etik Kedokteran - Ramlan Mochtar, Ramlan Mochtar (Universitas Gadjah Mada, 1981)
The author reminds the Indonesian medical profession of various codes of medical ethics guiding medical practice and research. Among others the following codes are discussed: the Hippocratic Oath, the Declaration of Geneva, the International Code of Medical Ethics, the Indonesian Code of Medical Ethics, the Declaration of Helsinki, the Declaration of Sydney, and the AMA Prin ciples of Medical Ethics.Key Words: medical ethics - Hippocratic Oath - Oath of Indonesian Physicians - biomedical research - statement on death